MICROENCAPSULATION OF PROBIOTIC Lactobacillus plantarum AND ANALYSIS OF ITS MANNOSE SPECIFIC ADHESIN GENE EXPRESSION - Novik Nurhidayat (Pusbindiklat - LIPI, 2012)
Infectious disease remains as a prominent health problem and worsened by the emerging antibiotic resistance. Probiotic has been an alternatievly popular application. Lactobacillus plantarum mar8 isolated from tropical fruit showed a stable mannose specific adhesin (MSA) activity in term of competing for and inducing immunity to infecting pathogen. This research focused on coating the probiotic with dextrin in fruit juice using a spraydrying technique to produce microencapsulated probiotic. The microencapsulation using 5% dextrin in either passion fruit or orange juice produced more compact capsule and supported higher probiotic viability. The microencapsulated probiotic expressed MSA gene for at least 10 generation indicating conserved function of probiotic.